(untitled) (CIPEEX, 2023)
The present work presents the ’State of the Art’ scheduled for the development of a Master’s Thesis being carried out in the stricto sensu Graduate Program in Environmental Sciences at the Evangelical University of Goiás (UniEVANGÉLICA). The agenda records the importance of the Ecological ICMS for the protection, preservation, and promotion of biodiversity present in the Integral Protection Unit, designated as the João Leite State Park (Pejol). To achieve success, a deductive approach was employed, enhanced by bibliographic and documentary techniques, which allowed for the development of descriptive and explanatory research.